The time-series properties of aggregate consumption: implications for the costs of fluctuations - Ricardo Reis (Princeton University, Woodrow Wilson School of Public and International Affairs, 2005)
While this is typically ignored, the properties of the stochastic process followed by aggregate consumption affect the estimates of the costs of fluctuations. This paper pursues two approaches to modelling aggregate consumption dynamics and to measuring how much society dislikes fluctuations, one statistical and one economic. The statistical approach estimates the properties of consumption and calculates the cost of having consumption fluctuating around its mean growth. The paper finds that the persistence of consumption is a crucial determinant of these costs and that the high persistence in the data severely distorts conventional measures. It shows how to compute valid estimates and confidence intervals. The economic approach uses a calibrated model of optimal consumption and measures the costs of eliminating income shocks. This uncovers a further cost of uncertainty, through its impact on precautionary savings and investment. The two approaches lead to costs of fluctuations that are higher than the common wisdom, between 0.5% and 5% of per capita consumption.
Keywords: E21; E32; E60; 330; Costs of fluctuations; Models of aggregate consumption; Consumption persistence; Gesamtwirtschaftlicher Konsum; Konsumtheorie; Zeitreihenanalyse; Konjunktur; Soziale Kosten